Effects of Abnormal-Sterol Accumulation on Ustilago maydis Plasma Membrane H(+)-ATPase Stoichiometry and Polypeptide Pattern - Hernández, Agustín (American Society for Microbiology, 1998)
Accumulation of 14α-methylated sterols or Δ(8)-sterols in Ustilago maydis affected three aspects of the plasma membrane H(+)-ATPase. Proton transport was reduced in Δ(8)-sterol-accumulating samples, due to an altered H(+)/ATP stoichiometry. ATP hydrolytic activity was increased, but no direct correlation with the extent or type of abnormal sterol accumulated could be drawn. Finally, Western blot analysis with antibodies against yeast PMA1 revealed a second lighter band (99-kDa band) in all samples from abnormal-sterol-accumulating sporidia. The conclusions are that the 99-kDa band and a reduced stoichiometry are directly linked to the presence of abnormal sterols, while changes in hydrolytic activity are linked only indirectly.